Lebanon : Country Water Sector Assistance Strategy, 2012-2016 - World Bank (Washington, DC, 2013)
The core objective of the Country Water Sector Assistance Strategy (CWSAS) is to define an operational plan for World Bank involvement in Lebanon's water sector 2012-2016 in support of implementation of national water strategy. In March 2012, the Lebanese Government officially adopted its National Water Sector Strategy (NWSS), which was prepared by a high-level team of Lebanese experts and debated amongst stakeholders. Drawing on lessons learned from past Bank involvement (both projects and sector work), and on the Bank-Government Country Partnership Strategy (CPS), the CWSAS looks at the water sector through the lens of economic growth, poverty reduction and sustainability, identifying in Government's strategy how investment might play a transformative role, accompanying and helping to drive key institutional reforms. Recognizing that restrictions of political economy are real and must be taken into consideration, the CWSAS highlights how implementation of the strategy might be prioritized and sequenced, how ownership might be strengthened through further stakeholder involvement, especially at the local level, and how capacity building within institutions could bring greater likelihood of successful reform implementation. This combination of targeted investment and capacity building accompanying step-by-step implementation of a sequenced and consensual set of priority reforms could have a transformational impact on service delivery and on growth, poverty reduction and sustainability. Supporting reform and investment within the NWSS is a priority because of the high economic, social and political costs of current performance. Improved water service delivery will help reduce poverty and inequity, and contribute to gross domestic product (GDP), exports and employment growth.